Factors associated with the frailty syndrome in elderly individuals living in the urban area - Maycon Sousa Pegorari; Darlene Mara dos Santos Tavares (Universidade de São Paulo, 2014)
METHODS: this cross-sectional, observational and analytical household survey was conducted with 958 elderly individuals living in the urban area. The Brazilian version of the Functional Assessment Questionnaire and Multidimensional Scales (Depression, Katz and Lawton brief geriatric versions) were used, together with the Phenotype of Frailty developed by Fried. Descriptive analysis was performed along with a bivariate and multinomial logistic regression model (p<0.05).RESULTS: a total of 313 (32.7%) non-frail elderly individuals were found in addition to 522 (55.4%) pre-frail and 128 (12.8%) frail individuals. Factors associated with pre-frailty and frailty, respectively, included: being 70├ 79 years old and 80 years old or older; using 1├ 4 medications and 5 or more; greater number of morbidities, functional disability for instrumental activities of daily life, and negative self-perception. The absence of a partner was associated with pre-frailty while hospitalization in the last year, functional disability for basic activities of daily life and indication of depression were associated with frailty.CONCLUSION: pre-frailty and frailty conditions presented a percentage higher than that reported by Brazilian studies and are associated with health-related variables. These variables can be prevented with interventions directed to the health of elderly individuals.